Music genre classification using back-propagation neural network with fixed processing window size - Lee, Lay Cheng, author; Md. Shah Salam, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik & Multimedia)) - Universiti Teknologi Malaysia, 2012